Enablers and disablers to plug-in electric vehicle adoption in India: Insights from a survey of experts. (November 2021) - Dua, Rubal; Hardman, Scott; Bhatt, Yagyavalk; Suneja, Dimpy
Abstract: The Indian government is considering plug-in electric vehicle (PEV) deployment as one solution to address the issues of air pollution, energy security, and climate change. We investigate the potential for PEV adoption in India, the challenges in meeting the country's goals and ways to overcome them. We utilize a survey of 51 experts in the Indian light-duty vehicle (LDV) ecosystem to address these questions. The majority of experts indicate that India will marginally miss its 30% PEV sales target by 2030. The main reasons cited for this are PEVs' high upfront cost, a lack of policies promoting PEVs and a lack of charging infrastructure. Experts believe lack of domestic PEV battery and manufacturing supply chains will limit the supply of low-cost PEVs to the Indian market. The lack of land availability and high land rent prices in Indian cities is cited as the major barrier to the establishment of charging infrastructure. The experts view a PEV sales mandate and incentives, such as 'feebates, ' as the most effective policy levers, while believing a ban on conventional vehicle sales by 2030 was unlikely. The findings hold significance for understanding the future of India's LDV sector and the associated energy and environmental impacts, which have global implications.